1996
DOI: 10.2307/3432714
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine-Associated Immunosuppression in Prefledgling Caspian Terns and Herring Gulls from the Great Lakes: An Ecoepidemiological Study

Abstract: The objectives of this study were to determine whether contaminant-associated immunosuppression occurs in prefledgling herring gulls and Caspian terns from the Great Lakes and to evaluate immunological biomarkers for monitoring health effects in wild birds. During 1992 to 1994, immunological responses and related variables were measured in prefledgling chicks at colonies distributed across a broad gradient of organochlorine contamination (primarily polychlorinated biphenyls), which was measured in eggs. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
2
8

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 63 publications
3
52
2
8
Order By: Relevance
“…It has been well established that OCs affect immune cells and immune function in laboratory-exposed animals (Bruckner et al 1973; Hoffman et al 1996; Segre et al 2002; Smits et al 2002). Furthermore, associations have been documented between OC concentrations, such as TEQs, ∑PCBs, and DDE, and an elevation in the heterophil:lymphocyte ratio in juvenile herring gulls (Grasman et al 2000b) and Caspian terns from the Great Lakes (Grasman et al 1996). Male American kestrels experimentally exposed to PCBs exhibited increased WBC counts (Smits et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well established that OCs affect immune cells and immune function in laboratory-exposed animals (Bruckner et al 1973; Hoffman et al 1996; Segre et al 2002; Smits et al 2002). Furthermore, associations have been documented between OC concentrations, such as TEQs, ∑PCBs, and DDE, and an elevation in the heterophil:lymphocyte ratio in juvenile herring gulls (Grasman et al 2000b) and Caspian terns from the Great Lakes (Grasman et al 1996). Male American kestrels experimentally exposed to PCBs exhibited increased WBC counts (Smits et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Potential immunotoxicity of OCs has been illustrated by changes in white blood cell (WBC) counts in both laboratory-exposed animals such as mice and seals (de Swart et al 1995; Segre et al 2002), as well as environmentally exposed wildlife and humans (Grasman et al 1996; Lawton et al 1985). An increase in the heterophil:lymphocyte ratio has also been shown to be an indicator of general stress in chickens (Gross and Seigel 1983) and of disease in sea turtles (Aguirre et al 1995; Cray et al 2001; Work et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ®rst report of plasma T 4 measurements in birds from the Great Lakes was for herring gull chicks collected in the early to mid 1990s. This study found no differences in plasma T 4 , in either species, between high and low PCB sites (Grasman et al, 1996). However, recent studies of pipped embryos and pre-¯edgling herring gulls collected in 1998 ± 2000 showed evidence of hypothyroidism.…”
Section: Toxicant (7)mentioning
confidence: 86%
“…Other toxic effects include enlarged thyroid glands in fish and suppression of T-cell-mediated immunity following prenatal exposure to organochlorines in herring gull and Caspian terns (Leatherland, 1992;Grasman et al, 1996). Table 2 lists adverse health effects in wildlife that are associated with exposure to contaminants in the Great Lakes (U.S. EPA, 1992).…”
Section: Wildlife Populationsmentioning
confidence: 99%